The contribution of various mechanisms to mRNA diversity of human fusion oncogene RUNX1-RUNX1T1 - Ilyushonak, Ilya M.; Migas, Alexandr A.; Sukhareuski, Andrei Yu.; Schneider, Aksana D.; Grinev, Vasily V. (Experimental Biology and Biotechnology, 2019)
In this work, we used a comprehensive set of the fusion oncogene RUNX1-RUNX1T1 alternative exons to analyze the patterns of its mRNA generation. We found that the waste majority of alternative exons are modified variants of canonical exons, and the transcripts, including such exons, have a very low expression level. The «hot regions», including exons 4a, 6, 8b, 9, 11 and 12, produces about 80 % of such variants. Also we described a new transcription start region of RUNX1-RUNX1T1 and provide the evidences of co-expression of the fusion RNAs with normal and shortened 3′-UTRs in leukemic cells.